Effect of soil-structure interaction on fragility analysis of composite shear wall buildings - Phadnis, P.P.; Karjinni, V.V. (Journal of Structural Engineering, 2024)
Due to rapid development in civilization, it is obliged to construct structures on all existing types of soil. As all structures are directly in contact with the soil, interaction among the structure, foundation and soil medium underneath the foundation changes the real behaviour of structure very much as obtained by the concern of structure alone. Hence, the effects of soil flexibility have to be considered in the seismic analysis to ensure the seismic safety of the structure. The soil medium represented as a Winkler’s model according to ASCE/SEI 41-06. Modal pushover analysis is performed and characteristics of the capacity curve are compared by incorporating Soil-Structure Interaction (SSI) with fixed base frame-composite shear wall system. Damage probabilities determined from fragility curves of models are also compared.